Association of dietary patterns with serum phosphorus in maintenance haemodialysis patients: a cross-sectional study - Khor, Ban Hock; Sualeheen, Ayesha; Sahathevan, Sharmela; Chinna, Karuthan; Abdul Gafor, Abdul Halim; Bavanandan, Sunita; Goh, Bak Leong; Morad, Zaki; Mat Daud, Zulfitri 'Azuan; Khosla, Pramod; Yee, Angela Moon Wang; Karupaiah, Tilakavati (Nature Publishing, 2020)
Sources of dietary phosphate differentially contribute to hyperphosphatemia in maintenance haemodialysis (MHD) patients. This cross-sectional study in Malaysia investigated association between dietary patterns and serum phosphorus in MHD patients. Dietary patterns were derived by principal component analysis, based on 27 food groups shortlisted from 3-day dietary recalls of 435 MHD patients. Associations of serum phosphorus were examined with identified dietary patterns. Three dietary patterns emerged: Home foods (HFdp), Sugar-sweetened beverages (SSBdp), and Eating out noodles (EO-Ndp). The highest tertile of patients in HF (T3-HFdp) pattern significantly associated with higher intakes of total protein (p = 0.002), animal protein (p = 0.001), and animal-based organic phosphate (p < 0.001), whilst T3-SSBdp patients had significantly higher intakes of total energy (p < 0.001), inorganic phosphate (p < 0.001), and phosphate:protein ratio (p = 0.001). T3-EO-Ndp patients had significantly higher intakes of total energy (p = 0.033), total protein (p = 0.003), plant protein (p < 0.001), but lower phosphate:protein ratio (p = 0.009). T3-SSBdp patients had significantly higher serum phosphorus (p = 0.006). The odds ratio of serum phosphorous > 2.00 mmol/l was significantly 2.35 times higher (p = 0.005) with the T3-SSBdp. The SSBdp was associated with greater consumption of inorganic phosphate and higher serum phosphorus levels.